Potential nutrition contributions to exercise-associated muscle cramping in four recreational half-marathoners: A case series - Hanson, Jennifer Ann; Dole, Andrew (My University, 2021)
Objectives: Nutrition-related practices and outcomes vary dramatically between athletes, and traditional beliefs regarding the role of electrolytes and hydration in exercise-associated muscle cramping (EAMC) may be hindering meaningful prevention strategies. The aim of this study was to characterize the role of carbohydrate (CHO), energy, and exertion level, in conjunction with electrolyte and hydration status to assess the role of these possible predictors of EAMC. Methods: A case study series approach was used to capture pre-race and on-course food and beverage intake, pre and post-race body weight, relative perceived exertion (RPE), and history of EAMC for four recreational runners prior to and during a half-marathon race. Results: CHO intake, energy intake, and hydration status varied among the runners with one occurrence of EAMC. Reported pre-race CHO intake for all but one runner fell below 5 g/kg/day. Weight loss during the race was between 1.23-3.03%. Two of the four runners reported a prior history of EAMC, one of which experienced EAMC during the race. The two runners with a prior history of EAMC, also reported the lowest 3-day energy and CHO intakes. The one runner who encountered an EAMC did not experience the greatest net race sodium loss. However, this runner did have the greatest race weight loss, the greatest race sweat loss, the longest duration of activity, the lowest RPE, and suboptimal energy and CHO intakes. Conclusions: The observed case of EAMC does not appear to be entirely inconsistent with the traditional dehydration/ electrolyte loss theory. However, the in-depth characterization of each runner illustrates the complex interaction of potential predictors and also generates questions regarding the potential contribution of suboptimal energy and CHO intakes.
Keywords: Carbohydrate; Electrolytes; Sodium; Muscle cramp; Dehydration; Running